Managerial Competencies and Growth of Small and Medium Enterprise (SMEs) in Abuja Metropolis, Nigeria - Anoke, Amechi Fabian; Onu, Anthonia Nkechi; Agagbo, Ogugua Chinyere (Goodwood Publishing, 2022)
Purpose: This study aimed at investigating the effect of managerial competencies on the growth of SMEs in Abuja Metropolis, Nigeria. Research methodology: The study adopted Raosoft to determine a sample size of 395. A structured questionnaire was used for data collection, while regression was used for data analysis. Results: It was found that both technical and personal competencies have a positive and strong effect on the growth of SMEs, while conceptual skills recorded a negative and insignificant effect on the growth of SMEs in the Abuja Metropolis. Limitations: This study is limited to SMEs operators in Abuja Metropolis (the political capital of Nigeria), Leaving Lagos (the economic capital of Nigeria untouched). It is only when Lagos is covered that one can give a clear direction if Nigerian SMEs operators are changing with the changing business world. Contribution: Operators, owners as well as policymakers in SMEs are expected to benefit from this study as it will serve as an eye-opener to the hidden and untapped potentials embedded in the proper application of managerial skills.